2022
DOI: 10.3390/catal12080891
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Pt Nanoparticles by Ascorbic Acid on Composite Electrospun Polyacrylonitrile-Based Carbon Nanofiber for HT-PEM Fuel Cell Cathodes

Abstract: The efficient use of renewable energy sources requires development of new electrocatalytic materials for electrochemical energy storage systems, particularly fuel cells. To increase durability of high temperature polymer electrolyte fuel cell (HT-PEMFC), Pt/carbon black based catalysts should be replaced by more durable ones, for example Pt/carbon nanofibers (CNF). Here, we report for the first time the quantitative ascorbic acid assisted deposition of Pt onto electrospun polyacrylonitrile-based CNF composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Due to their instability during the FC operation in phosphoric acid media at a sufficiently high temperature (150–200 °C) at high potential, their replacement with more stable carbon nanostructured materials is required. Recently, we have shown that carbon nanofiber (CNF) mats (self-supporting entire non-woven carbon nanofiber material) based on polyacrylonitrile (PAN) or polyheteroarylenes can be used as electrocatalyst support for Pt nanoparticles and applied as electrodes for the high-temperature polymer-electrolyte membrane FC [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their instability during the FC operation in phosphoric acid media at a sufficiently high temperature (150–200 °C) at high potential, their replacement with more stable carbon nanostructured materials is required. Recently, we have shown that carbon nanofiber (CNF) mats (self-supporting entire non-woven carbon nanofiber material) based on polyacrylonitrile (PAN) or polyheteroarylenes can be used as electrocatalyst support for Pt nanoparticles and applied as electrodes for the high-temperature polymer-electrolyte membrane FC [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%